Perlindungan Hukum bagi Konsumen dalam Transaksi Jual Beli Online Ditinjau dari Hukum Perikatan - Alecya Maruli Semaria Nababan; Eldrida Joan Karnois; Muhamad Ajie Nurdiansyah; Ratu Sheebakayla (Program Studi Ilmu Hukum, Universitas Kuningan, 2024)
This abstract discusses legal protection for contracts in the context of online buying and selling transactions as an effort to protect consumers. In the digital era, online buying and selling transactions are increasingly widespread and present new challenges in the field of contract law. Legal protection is very important to ensure consumer rights are protected from unfair trade practices, fraud and other violations. This article analyzes existing regulations, the role of electronic agreements, and the dispute resolution mechanisms available to consumers. Thus, it is hoped that the legal protection of engagement can provide security and trust for consumers in carrying out online transactions